STED nanoscopy with mass-produced laser diodes - Schrof, Susanne; Staudt, Thorsten M.; Rittweger, Eva; Wittenmayer, Nina; Dresbach, Thomas; Engelhardt, Johann; Hell, Stefan (Optics express, 2011)
We show that far-field fluorescence nanoscopy by stimulated emission depletion (STED) can be realized with compact off-the-shelf laser diodes, such as those used in laser pointers and DVDs. A spatial resolution of 40-50 nm is attained by pulsing a 660 nm DVD-diode. The efficacy of these low-cost STED microscopes in biological imaging is demonstrated by differentiating between clusters of the synaptic protein bassoon and transport vesicles in hippocampal neurons, based on the feature diameter. Our results facilitate the implementation of this all-molecular-transition based superresolution method in many applications ranging from nanoscale fluorescence imaging to nanoscale fluorescence sensing.
Gesehen am 27.10.2022